2001
DOI: 10.2116/analsci.17.37
|View full text |Cite
|
Sign up to set email alerts
|

A Glass Capillary Ultramicroelectrode with an Electrokinetic Sampling Ability

Abstract: A glass capillary ultramicroelectrode (tip diameter ≈1.2 µm) having an electrokinetic sampling ability is described. It is composed of a pulled glass capillary filled with an inner solution and three internal electrodes (Pt working and counter electrodes and an Ag/AgCl reference electrode). The voltammetric response of the capillary electrode is based on electrokinetic transport of analyte ions from the sample solution into the inner solution across the conical tip. It was found that the electrophoretic migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…The environmental limit of inorganic mercuric from the United States Environmental Protection Agency (US EPA) in drinking water is below 2 ppb (2 μg/L) http://www.epa.gov/ogwdw000/contaminants/dw_contamfs/mercury.html. Mercury content in human blood is normally within the range of 0.87 to 3.51 μg/L [34,35] and the warning level of mercury in human blood is 22.8 to 30 μg/L [34,36]. The reproducible, rapid and dose-dependent responsiveness of these genes to a range of HgCl 2 concentrations from 10 to 200 μg/L suggested that these genes can be potentially used as robust biomarkers in combination with analytical chemistry detection of mercury for investigating and assessing the severity of mercury exposure.…”
Section: Resultsmentioning
confidence: 99%
“…The environmental limit of inorganic mercuric from the United States Environmental Protection Agency (US EPA) in drinking water is below 2 ppb (2 μg/L) http://www.epa.gov/ogwdw000/contaminants/dw_contamfs/mercury.html. Mercury content in human blood is normally within the range of 0.87 to 3.51 μg/L [34,35] and the warning level of mercury in human blood is 22.8 to 30 μg/L [34,36]. The reproducible, rapid and dose-dependent responsiveness of these genes to a range of HgCl 2 concentrations from 10 to 200 μg/L suggested that these genes can be potentially used as robust biomarkers in combination with analytical chemistry detection of mercury for investigating and assessing the severity of mercury exposure.…”
Section: Resultsmentioning
confidence: 99%
“…8 Improvements of the spatial dissolution of L-glutamate measurements by miniaturizing the size of sampling probe and/or that of enzyme-based electrodes are important, because the neuronal activity that releases and metabolizes L-glutamate is a very fast event, 10 and hence the concentration of Lglutamate detected at a sensing probe depends on the location and distance of the probe from the neurons. For the purpose of miniaturizing the size of the sensing probes, pulled glass capillaries 27,28 have a unique feature: the tip diameters range from submicro-to several µm, and the glass surface has an affinity to lipids and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…It must be mentioned that on MWCNT-based films, well-defined CV curves of [Fe (CN) 6 ] 3−/4− were obtained with peak-to-peak potential separation equal to that which corresponds to Nernstian oneelectron transfer reaction (ΔE p ≈0.059 V) [24]. Furthermore, the detection limit of MWCNT-based films on [Fe (CN) 6 ] 3−/4− was determined to be about 0.80 μM, which was much better compared to that determined on other electrodes reported in literature [25]. SEM was used for the analysis of the structure and surface of MWCNT-based films.…”
Section: Preparation and Characterization Of Mwcnt-based Filmsmentioning
confidence: 62%